Practicality, support or premeditated calculation in the digital age: the case of Ecuador - Luque González, Arturo (Revista Venezolana de Gerencia, 2021)
This paper aims to analyze the attitudes among young Ecuadorians with regard to processes of technological practicality. It seeks to identify the turning points in the decision-making process regarding the transfer of data and to examine the associated conceptual debate surrounding the role of related participants, such as governments, supranational organizations, transnational companies and end-users. Interviews were conducted with 299 university students in the city of Ambato, Ecuador, using quantitative techniques. The participants stated that they were aware of practicality but not of its effects and limitations, indicating that not everyone would be willing to give up part of their privacy in return for benefits in frequently used applications such as Facebook, WhatsApp or Netflix. Generally, participants felt dominated by technology, which often masks the processes of dependency associated with the costs and custody of data surrendered in exchange for a benefit. Issues of fairness and security in the treatment of data and the uneven coverage of services highlight a need for greater regulation of technological platforms.